2019
DOI: 10.3390/met9040471
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Forces in Continuous Casting of Steel Slabs

Abstract: This paper reviews the current state of the art in the application of electromagnetic forces to control fluid flow to improve quality in continuous casting of steel slabs. Many product defects are controlled by flow-related phenomena in the mold region, such as slag entrapment due to excessive surface velocity and level fluctuations, meniscus hook defects due to insufficient transport of flow and superheat to the meniscus region, and particle entrapment into the solidification front, which depends on transvers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 113 publications
(330 reference statements)
1
43
0
Order By: Relevance
“…Fourteen research articles have been published in this Special Issue of Metals. Twelve of these [1][2][3][4][5][6][7][8][9][10][11][12] relate to the continuous casting of steel, a general schematic for which is shown in Figure 1. As is evident from this figure, the overall process consists of a ladle and a tundish through which molten steel passes, a cooling mould region where solidification starts and at which electromagnetic stirring (EMS) may be applied, secondary cooling regions where water is sprayed on the solidified steel, a so-called strand electromagnetic stirrer, a further region at which final EMS is applied, and withdrawal rollers, by which point the steel has completely solidified.…”
Section: Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen research articles have been published in this Special Issue of Metals. Twelve of these [1][2][3][4][5][6][7][8][9][10][11][12] relate to the continuous casting of steel, a general schematic for which is shown in Figure 1. As is evident from this figure, the overall process consists of a ladle and a tundish through which molten steel passes, a cooling mould region where solidification starts and at which electromagnetic stirring (EMS) may be applied, secondary cooling regions where water is sprayed on the solidified steel, a so-called strand electromagnetic stirrer, a further region at which final EMS is applied, and withdrawal rollers, by which point the steel has completely solidified.…”
Section: Contributionsmentioning
confidence: 99%
“…On the other hand, Ni et al [5] present a numerical study on the influence of a swirling flow tundish on multiphase flow and heat transfer in the mould, whereas Qin et al [7] conduct a simulation study on the flow behavior of liquid steel in a tundish with annular argon blowing in the upper nozzle. Su et al [9] use machine-learning techniques for mold-level prediction by means of variational mode decomposition and support vector regression (VMD-SVR), whereas Cho and Thomas [1] review the literature on electromagnetic forces in continuous casting of steel slabs. Yin et al [10] consider modelling on inclusion motion and entrapment during full solidification in a curved billet caster, while Long et al [4] develop a combined hybrid 3-D/2-D model for flow and solidification prediction during slab continuous casting.…”
Section: Contributionsmentioning
confidence: 99%
“…And after reaching the active region of the traveling magnetic field, the molten steel is pushed by the horizontal rotating forces and restrained from the surrounding mold walls, making a strong rotational flow around the wall in the upper area of the mold. In theory, this flow pattern not only ensures that the molten steel in the upper area of the mold is active, which facilitates the uniform heat transfer and the removing of non-metallic slag, and also avoids the impact position of the steel jet too deep, which is beneficial to reduce the penetration depth of inclusions [28]. strong impinging jets, which flow to the mold narrow-face at a certain angle and speed without applying electromagnetic driving.…”
Section: Analysis Of Flow Patternmentioning
confidence: 99%
“…In fact, recent studies have shown that the appropriate use of combined stirring and braking has the potential to optimize the flow of molten steel and to compensate for the limitations of a single electromagnetic field [24,25]. Multifunction electromagnetic driving which combines EMS and EMBr is the development trend of the current control technology of steel flow in a continuous casting mold [26][27][28][29]. However, there are few studies on the steel/slag interface behavior under multifunction electromagnetic driving.…”
Section: Introductionmentioning
confidence: 99%
“…This has the potential for comprehensive online control of the molten steel flow, which is responsible for many solidification defects, through its effects on superheat transport, initial solidification, particle transport and capture, surface quality, grain structure, and steel composition distribution. 18 This article reviews the various solidification defects in continuous casting and their formation mechanisms. It then focuses on the effects of electromagnetic fields on the solidification-related phenomena, which influence the formation of these defects.…”
Section: Introductionmentioning
confidence: 99%